Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing